Implementasi Penegakan Hukum Tindak Pidana Prostitusi di Kembang Kuning, Kota Surabaya - Rivaldi Anna Mahmuddi; Waluyo (Jurnal Hukum Lex Generalis, 2025)
The issue of prostitution continues to be a controversial matter in the City of Surabaya. Although the municipal government has imposed a prohibition, the practice of prostitution still persists in Surabaya, particularly in the Kembang Kuning area. This study examines the implementation of legal measures concerning prostitution in Kembang Kuning, as well as the various challenges encountered in achieving effective law enforcement. The research employs an empirical legal method by combining conceptual frameworks and statutory analysis. In terms of legal substance, the practice of prostitution is explicitly prohibited under Surabaya Municipal Regulation No. 7 of 1999 and Municipal Regulation No. 2 of 2020. Violations of these regulations are categorized as minor criminal offenses, processed through summary proceedings, and enforced by the Civil Service Police Unit (Satpol PP). Furthermore, the study reveals that the main challenges include sanctions that are insufficiently severe to serve as an effective deterrent, and the limited authority of Satpol PP, which only extends to the enforcement of conventional prostitution cases and does not cover practices conducted through digital platforms. This situation has resulted in a legal culture characterized by weak compliance, particularly with regard to the prohibition of prostitution in Surabaya.